The Celebrity Effect: The Influence of Celebrity Endorsements on Nepali Consumers - Maharjan, Rubi; Paudel, Udaya Raj; Basyal, Devid Kumar (Quest Journal of Management and Social Sciences, 2025)
Purpose: The effectiveness of celebrity endorsement in advertising continues to be a subject of ongoing debate. This study aims to analyse the impact of celebrity endorsement on customers' purchase intentions in Nepal, with particular emphasis on the mediating roles of brand credibility and consumer attitude. Methods: This study used an explanatory research approach. Convenience sampling is employed for the study using the non-probability sampling technique. Data were collected from 401 respondents using structured questions administered through the KOBO toolbox. Subsequently, the collected data were analysed employing Excel and SmartPLS 4.0. Findings: Trustworthiness and Expertise of celebrities significantly influence purchase intentions. This effect is mediated by both brand credibility and customer attitudes. Although celebrity attractiveness also boosts purchase intentions via customer attitudes, it does not have a similar impact when mediated by brand credibility alone. Key challenges include mismatches between the celebrity's image and the product and the dilution of trust due to celebrity overexposure. These can be addressed by selecting celebrities who authentically use the product and aligning the product with celebrities whose images fit the intended market. Conclusion: Celebrity trustworthiness and expertise significantly impact consumer purchase intentions, with brand credibility and customer attitudes acting as mediators. While celebrity attractiveness can boost intentions through customer attitudes, its effect is weaker when mediated solely by brand credibility. Brands should select celebrities whose image aligns with the product and target market, avoiding overexposure or mismatched associations to maintain trust and credibility. Keywords: Celebrity Endorsement, Customer Purchase Intention, Brand Credibility, Attitude, PLS-SEM, Trustworthiness, Expertise, Attractiveness, Nepal